Amino-Functionalized Wood Aerogel for Efficient Removal of Copper Ions from Water. (18th June 2021) - Meng, Junwang; Guan, Hao; Dai, Xinjian; Wang, Xiaoqing
Abstract : Developing bio-based adsorbents for efficient removal of heavy metal ions from water has attracted increasing attention due to their abundance, low cost, and sustainability. However, most of these adsorbents are in powdered or granular forms, suffering from difficult regeneration and poor recyclability. Here, we report a highly porous three-dimensional amino-functionalized wood aerogel for efficient heavy metal adsorption. The amino-functionalized wood aerogel was prepared from natural balsa wood via a delignification treatment, followed by TEMPO-mediated oxidation of the delignified wood and then grafting polyethylenimine (PEI) onto the oxidized cellulose skeleton. The obtained amino-functionalized wood aerogel possessed a unique porous lamellar structure with a low bulk density of 77.2 mg/cm 3 and high porosity of 94.9%. Benefiting from its high porosity and the introduced amino groups on the cellulose skeleton, the amino-functionalized wood aerogel exhibited a maximum Cu(II) adsorption capacity of 59.8 mg·g −1, which was significantly higher than those of the TEMPO-oxidized wood aerogel and natural balsa wood. The adsorption process can be well described by the pseudo-second-order and Langmuir isotherm models, indicating that the Cu(II) adsorption by the PEI@wood aerogel was dominated by a monolayer chemisorption process. The developed amino-functionalized wood aerogel provides new insights for the design of efficient and low-cost monolithic absorbents for heavy metal remediation.